Os incomodados que resistem: contradições e territoriali-dades camponesas no Projeto de Irrigação Várzeas de Sousa na Paraíba - Farias, Arethusa Eire Moreira de (2010)
The paper purports to examine the conflict over land between peasants and the State Government in the Irrigated Meadows Sousa (PIVAS) conceived in the 1950s and formalized in the late 1990s. The aim of the PIVAS is the production of irrigated fruits for export. For some authors the genre of waterbuck projects are part of the restructuring of the productive base of the Northeast. In 2002 the work was stopped by order of the Court of Audit (TCU) for finding irregularities in 2004 and started the conflict over land played by peasant families motivated by dissatisfaction and articulated by social movements. In 2010 the peasants' struggle six years old. The entry of the families in the productive process of PIVAS represents both a contradiction of the project as social movements, and a strategy of silent struggle, and it is in this context that guides the central objective of this research: Analyze the conflict over land played in the waterbuck by peasant families and the state, highlighting the points of contradiction in the formation of peasant territoriality for negotiation with the State Government and INCRA. As a result of the contradictions of agribusiness and strategies of the peasants there is a new subject peasant who comes to merge the mosaic of national classifications peasant, the farmer irrigating the meadow Sousa.